2010
DOI: 10.2478/s11772-010-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

Dipole and quadrupole surface plasmon resonance contributions in formation of near-field images of a gold nanosphere

Abstract: Multipolar plasmon optical excitations at spherical gold nanoparticles and their manifestations in the particle images formatted in the particle surface proximity are studied. The multipolar plasmon size characteristic: plasmon resonance frequencies and plasmon damping rates were obtained within rigorous size dependent modelling. The realistic, frequency dependent dielectric function of a metal was used. The distribution of light intensity and of electric field radial component at the flat square scanning plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Additionally, we endeavored to keep the size of the AuNPs below the threshold for electric quadrupole resonance, simplifying the analysis of the spectra. AuNPs possess electric quadrupole and magnetic dipole moments, and different authors have reported various thresholds for electric quadrupole resonance of AuNPs ranging from ~60 or 70 53,54 to ~150 nm Ø. 52 The AuNPs were synthesized as described in the Experimental Section.…”
Section: Mean Diameter Determination and Size Distributions Of The Comentioning
confidence: 99%
“…Additionally, we endeavored to keep the size of the AuNPs below the threshold for electric quadrupole resonance, simplifying the analysis of the spectra. AuNPs possess electric quadrupole and magnetic dipole moments, and different authors have reported various thresholds for electric quadrupole resonance of AuNPs ranging from ~60 or 70 53,54 to ~150 nm Ø. 52 The AuNPs were synthesized as described in the Experimental Section.…”
Section: Mean Diameter Determination and Size Distributions Of The Comentioning
confidence: 99%
“…As can be seen for Al, primarily due to the plasmonic NS in an environment with a higher refractive index than air ( n ZnO ~ 2.4) in the SC structure, the peaks of maximum near-field intensity are extended to higher wavelengths than the bulk case. The presence of multiple peaks at spectral maximum intensity can depend on numerous factors in the MNS, such as NP size distribution, NP distances, bipolar resonance, and higher modes such as quadrupole and longitudinal-transverse excitations [ 57 , 58 ]. As the height of the nanoparticles decreases in different modes of the O-group (O.1 to O.4), the location of the peaks shift so that the peaks become intensive at larger wavelengths.…”
Section: Resultsmentioning
confidence: 99%
“…UV-VIS diffuse reflectance spectra of SNDC fibers samples with variations in time of irradiation and microwave power are illustrated in ( Figure 2 ). Valley of the reflectance spectra in the range of 430–450 nm is due to the out plane quadrupole plasmon resonance and some partial color change are also due to localized surface plasmon resonance (LSPR) ( Kelly et al, 2003 ; Sherry et al, 2006 ; Shopa et al, 2010 ; Dankovich and Gray, 2011 ; Tang et al, 2012 ; Dankovich, 2014 ).…”
Section: Resultsmentioning
confidence: 99%